Improvement on bioleaching interfacial behavior between Bacillus mucilaginosus and vanadium-bearing shale by surfactant additive. Issue 6 (December 2022) - Cai, Zhenlei; Wang, Yue; Zhang, Yimin; Zheng, Qiushi
Abstract: Effects of surfactant SDS (Sodium Dodecyl Sulfate) on bacterial metabolism and vanadium leaching effect by Bacillus mucilaginosus ( B. mucilaginosus ) were explored. The results indicated that the bacteria adsorption dissolution effect and the organic acid dissolution effect could extract 29.12% and 35.21% of vanadium, respectively, which were 9.70% and 6.27% higher than those without SDS. SDS significantly enhanced the bacteria adsorption dissolution effect and the organic acid dissolution effect of B. mucilaginosus on vanadium-bearing shale, and the bacteria adsorption dissolution effect to improve the vanadium leaching efficiency was more remarkable. When the bioleaching time began to enter the bacteria stable growth phase and the stable pH phase, the EPS (Extracellular Polymeric Substances) concentration decreased by 73.1 mg/L and 68.2 mg/L under the action of SDS, respectively. However, the bacteria's adsorbance on the mineral surface increased by 0.07 × 10 9 cells/mL and 0.13 × 10 9 cells/mL, respectively. The improvement on the bacteria adsorption dissolution effect with SDS was then revealed. SDS decreased the secretion of EPS, reduced the bacterial agglomeration, increased the adsorption capacity of bacteria, and thereby strengthened the dissolution effect. Furthermore, it was found that the H + concentration in the leachate increased by 1.36 × 10 −5 mol/L and 4.33 × 10 −5 mol/L, respectively. The enhancement on the organic acid dissolution effect with SDS was also achieved. The increase of the organic carboxylic acid metabolites was beneficial to further remove the hydroxyl groups in the vanadium-bearing muscovite crystal lattice, and strengthen the destruction of the basic structure of silicon-oxygen tetrahedron and aluminum-oxygen octahedron, resulting in the release of vanadium. Graphical Abstract: ga1 Highlights: The bacteria adsorption dissolution effect was more remarkable in V extraction. SDS reduced EPS secretion and increased bacteria adsorbance on mineral surfaces. SDS enhanced the production of organic carboxylic acid metabolites by bacteria. Erosion on the mineral surface by bacteria was deepened with the addition of SDS.